Bupropion induced hypertensive crisis in a healthy male with no prior hypertension - Siddiq, Nadia; Abbas, Usama; Rauf, Noor Fatima; Waris, Barak; Butt, Nauman Ismat (International Journal of Pathology, 2025)
Background: Bupropion is a norepinephrine-dopamine reuptake inhibitor (NDRI) indicated in treatment of depression, attention deficit hyperactivity disorder (ADHD) and for smoking cessation. Although hypertension is a known side effect, hypertensive crises in previously normotensive individuals is rarely reported. Case Report: A 26-year-old male took bupropion for depressive symptoms during his exams, but his condition worsened after he started consuming excessive amounts of caffeine and energy drinks. The combination of bupropion and excessive caffeine intake led to hypertension and tachycardia. During his first visit to the emergency department, he presented with a blood pressure of 160/90 mmHg and a heart rate of 110 bpm. On a subsequent visit, these values had increased to 180/110 mmHg and 132 bpm, respectively. Workup ruled out other secondary causes. The symptoms resolved after discontinuation of bupropion. Conclusion: Clinicians should monitor blood pressure in all patients, including those without known cardiovascular risk.